(untitled) (LACCEI, 2024)
Currently, in Peru, 84% of companies importers are SMEs, which sell products manufactured in other countries to meet the needs of Peruvian consumers. The dynamism of this activity is high and in the course of the first ten months of 2022 the total value of imports amounted to more than US 50,580 million, being 20.8% higher than the same period in 2021. Without However, despite the growth in imports, there are various external factors such as the exchange rate, the decrease in productive capacity of manufacturing companies, the high transport costs, the decrease in income of the buyers and among others, which have generated a series of problems to importers among which can be identified are the increase in supply costs, decrease in inventory turnover, increased logistics costs and others. This has contributed to an increase in its costs. logistics, decrease in productivity, decrease in profitability and finally a loss of competitiveness. For the Therefore, to overcome the previous problems, it is proposed a methodology based on the demand forecast and the management of inventories that contribute to solving the problems of the level of stock, service level and productivity in companies shoe marketers and whose final consequence is the increase in the profitability and competitiveness of SMEs in the it was Post Covid-19.